OIIANDI, Eni Pulcinelli. As formas do silêncio: no movimento dos sentidos. Campinas, S. R: Editora da Unicamp, 1995, 189 p. - Bertolucci, Cely (Cadernos de Linguagem e Sociedade, 2010)
OIIANDI, Eni Pulcinelli. As formas do silêncio: no movimento dos sentidos. Campinas, S. R: Editora da Unicamp, 1995, 189 p.